Wearable Medical Devices: Application Status and Prospects - Xiaowen Wang; Yingnan Gao; Yueze Yuan; Yaping Wang; Anqin Liu; Sen Jia; Wenguang Yang (Micromachines)
Electronic skin (E-skin) refers to a portable medical or health electronic device that can be worn directly on the human body and can carry out perception, recording, analysis, regulation, intervention and even treatment of diseases or maintenance of health status through software support. Its main features include wearability, real-time monitoring, convenience, etc. E-skin is convenient for users to wear for a long time and continuously monitors the user’s physiological health data (such as heart rate, blood pressure, blood glucose, etc.) in real time. Health monitoring can be performed anytime and anywhere without frequent visits to hospitals or clinics. E-skin integrates multiple sensors and intelligent algorithms to automatically analyze data and provide health advice and early warning. It has broad application prospects in the medical field. With the increasing demand for E-skin, the development of multifunctional integrated E-skin with low power consumption and even autonomous energy has become a common goal of many researchers. This paper outlines the latest progress in the application of E-skin in physiological monitoring, disease treatment, human–computer interaction and other fields. The existing problems and development prospects in this field are presented.